Polish Preparatory Proceedings in Civil Cases: Written or Oral? Lessons to be Learned from Some Other Jurisdictions - Piszcz Anna (Studies in Logic, Grammar and Rhetoric, 2016)
In this paper a description of the model of Polish preparatory proceedings in civil cases will be presented. By looking at foreign examples of preparatory activities in civil cases first, we will be able to discern what potential advantages and disadvantages are associated with the written or oral (spoken) form of preparatory activities of court actors in the first stage of civil proceedings. In the second main part of the paper the author will turn to Polish counterparts of these preparatory activities and their form. The author will also deliberate on where a change is needed. She will also attempt to propose some measures that might be useful in the current condition of Polish civil proceedings.